Molecular insights into the structure forming properties of zein and a rheological comparison with hordein - Bhanu Devnani; Nicholle Kirsten Tan; Jeffrey M Sanders; John C Shelley; Francesca Moraca; Lutz Grossmann (Future Foods)
Prolamins are hydrophobic proteins extracted using water-ethanol mixtures, useful for texturing meat and cheese alternatives at low temperatures due to their self-aggregating properties. This study explored the rheological and structural properties of the corn prolamin zein under varying temperature and pH conditions and compared its rheological behavior to the barley prolamin hordein. Zein showed plasticization when heated, with plasticization temperatures ranging from 41.3 °C at pH 4 to 46.7 °C at pH 6. Texture maps indicated that zein formed brittle gels within the linear viscoelastic range and tougher structures at crossover, unlike hordein, which was more elastic and lacked a clear plasticization behavior (softening) during heating. These differences were linked to zein's hydrophobicity. Coarse-grained molecular dynamics simulations showed zein self-aligning into anisotropic protein structures during heating, with its radius of gyration increasing from Rg = 21 Å to Rg = 34 Å by heating. This study provided insights into the structuring of prolamins and highlighted the need to understand plasticization mechanisms to improve zein's functionality in food applications.